Energy Integration in Wastewater Treatment Plants by Anaerobic Digestion of Urban Waste: A Process Design and Simulation Study - Rocio Vicentin; Fernando Fdz-Polanco; Maria Fdz-Polanco (International Journal of Chemical Engineering)
The process simulation performed in the present study aimed at investigating energetically self-sufficient wastewater treatment plant of 500,000 population equivalents. To implement this, three different scenarios were evaluated using computational tools named GPS-X® and SuperPro®. They were designed based on municipal wastes recovery to energy generation and its utilisation within the facility. An anaerobic/anoxic/oxic process for biological treatment of wastewater was considered and mesophilic anaerobic digestion at different scenarios (1) primary sludge (PS) with waste activated sludge (WAS), (2) PS with thermally hydrolysed WAS, and (3) PS with WAS and organic fractions derived from municipal solid waste. The results from scenario 1 and scenario 2 showed only enough thermal energy to meet their demand (they reach only 44 and 52% of electrical self-sufficiency, respectively), while positive net thermal and electrical energy result in scenario 3 from codigestion of sewage sludge and the organic fraction of municipal solid waste. The main limitation of tools used is their lack of sensitivity to economies of scale and their dependence on real data used for process design to obtain more accurate results.